The Effectiveness of Project-Based Learning Models in Enhancing Critical Thinking Skills: A Literature Review - Nanda Aulia Pratiwi; Ni Ketut Anggriani; Dewa Dwi Pranahita (Indonesian Journal of Teacher Education, 2026)
Critical thinking skills are essential competencies in the 21st century that students must possess. The Project-Based Learning (PjBL) model is believed to be an effective pedagogical approach to develop these skills. This study aims to describe the trends and effectiveness of the PjBL model in enhancing students' critical thinking skills based on a literature review. This study employs a descriptive literature review approach by analyzing relevant scientific publications from the last ten years. A bibliometric analysis using VOSviewer was also conducted to map research topic trends. The analysis results indicate that research on PjBL and critical thinking has significantly increased. The PjBL model, whether implemented purely or integrated with other approaches such as STEM, is consistently proven effective in enhancing critical thinking skills across various educational levels and subjects. This effectiveness is driven by the PjBL syntax that emphasizes real project-based learning, collaboration, and problem-solving, which directly trains students' metacognitive and analytical aspects.